Surrealists in New York : Atelier 17 and the Birth of Abstract Expressionism - Darwent, Charles (London : Thames & Hudson, 2023)
c
t Chapter 4. Towards a new painting-- t Chapter 8. After.
Includes index
Keywords: Surrealism -- New York (State) -- New York -- History -- 20th century; Abstract expressionism -- United States -- History -- 20th century; New York (N.Y.) -- Intellectual life -- 20th century; Biographies